2011
DOI: 10.4310/cag.2011.v19.n5.a6
|View full text |Cite
|
Sign up to set email alerts
|

Curvature pinching estimate and singularities of the Ricci flow

Abstract: Abstract. In this paper, we first derive a pinching estimate on the traceless Ricci curvature in term of scalar curvature and Weyl tensor under the Ricci flow. Then we apply this estimate to study finite-time singularity behavior. We show that if the scalar curvature is uniformly bounded, then the Weyl tensor has to blow up, as a consequence, the corresponding singularity model must be Ricci flat with non-vanishing Weyl tensor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 25 publications
(41 reference statements)
3
24
0
Order By: Relevance
“…As an immediate consequently of Theorem 2.2 we obtain the following theorem that is an extension of Cao's result ( [6], Corollary 3.1).…”
Section: )supporting
confidence: 61%
See 1 more Smart Citation
“…As an immediate consequently of Theorem 2.2 we obtain the following theorem that is an extension of Cao's result ( [6], Corollary 3.1).…”
Section: )supporting
confidence: 61%
“…A well-known conjecture (see [6]) about the extension of RF states that (1.6) Is it true for lim sup…”
Section: Introductionmentioning
confidence: 99%
“…Remark 1.3. If we let h = Rc, then Theorem 1.1 is just as a special case of Knopf 's Ricci curvature pinching estimate [19] (see also [4]). Cao and H. Tran [5] observed that the Ricci flow solution with nonnegative isotropic curvature implies a Riemannian curvature pinching result:…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…This conjecture was settled for Kähler-Ricci flow by Zhang [57] and for type-I maximal solution of RF by Enders-Müller-Topping [10]. Cao [6] proved the following:…”
Section: Long Time Existence Of Rhfmentioning
confidence: 97%
“…List [27] and Müller [34] showed that, under the system of evolution equations 6) which is nonnegative. The evolution equations for other two functionals are derived in [25].…”
Section: Perelman-type Functionalsmentioning
confidence: 99%